2020
DOI: 10.33448/rsd-v9i7.4260
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre oclusopatias e hábitos parafuncionais na primeira infância

Abstract: Occlusopathies are a high prevalence problem characterized by a set of anomalies in the face of deviations in dental alignment, in the relationship between the dental arches and/or between the maxillary bones. The literature shows a direct relationship between occlusopathies and parafunctional habits in early childhood. From this perspective, understanding the etiology of occlusopathies to prevent or intercept these deviations becomes essential, in view of the difficulty in treatment for the correction of futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…As for the thumb-sucking habit, the prevalence this investigation was 8.9%, lower than what was found in the study by Matos et al 22 with 15.2%. The literature reports the development of this habit when there is an emotional need, especially in moments of tension, thus increasing the risk of AOB development 23 . This study found no statistical difference between AOB and thumbsucking or mouth breathing.…”
Section: Discussionmentioning
confidence: 99%
“…As for the thumb-sucking habit, the prevalence this investigation was 8.9%, lower than what was found in the study by Matos et al 22 with 15.2%. The literature reports the development of this habit when there is an emotional need, especially in moments of tension, thus increasing the risk of AOB development 23 . This study found no statistical difference between AOB and thumbsucking or mouth breathing.…”
Section: Discussionmentioning
confidence: 99%
“…A cobertura de serviços odontológicos pelo setor público é elementar na maior parte dos estabelecimentos e os procedimentos cobertos são os de menor complexidade. O setor privado, apesar de imperar na oferta de serviços, absorve apenas uma parte da população, que paga diretamente pelos serviços ou se enquadra dentro de planos de saúde, que em sua maioria não cobrem tratamentos ortodônticos, absurdamente por serem considerados tão somente estéticos 12 .…”
Section: Materiais E Métodosunclassified
“…Malocclusion, de ned as inadequate or abnormal dental alignment, not only gives rise to a problematic craniofacial relationship but also constitutes an important oral health problem worldwide [4]. Its prevalence ranges from 11-99% and may be associated with several factors, including genetic and environmental components [5][6][7][8].…”
Section: -Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), attaining adequate oral health is the gateway to general health, wellbeing and quality of life [2]. The impact of good oral health goes beyond the absence of pain or discomfort, through ensuring self-con dence, socialization, correct chewing and correct pronunciation [3].Malocclusion, de ned as inadequate or abnormal dental alignment, not only gives rise to a problematic craniofacial relationship but also constitutes an important oral health problem worldwide [4]. Its prevalence ranges from 11-99% and may be associated with several factors, including genetic and environmental components [5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation